A CASE REPORT: ENHANCING TARSAL AND MUSCULAR SUPPORT FOR ECTROPION CORRECTION IN TESSIER 3 AND 5 FACIAL CLEFT - Teuku Adifitrian; Hendra Tri Hartono; Agustina Indah Garnasih (Jurnal Rekonstruksi dan Estetik)
Highlights: